Adsorption of phenol from aqueous solution by using carbonised beet pulp - Dursun, G; Çiçek, H; Dursun, AY (Elsevier, 2005)
The beet pulp, a major low value by-product in sugar industry was used to prepare carbon for phenol adsorption. It was produced by carbonisation in N-2 atmosphere at 600 degrees C for 1.5 h. The surface area of beet pulp carbon was measured as 47.5 m(2) g(-1) by using BET method. The adsorption studies of phenol from aqueous solution on beet pulp carbon (BPC) have been studied in the range of 25-500 mg dm(-3) initial phenol concentrations and at the temperatures of 25, 40 and 60 degrees C. The maximum phenol adsorption capacity was obtained as 89.5 mg g(-1) at the temperature of 60 degrees C at pH=6.0. The Freundlich and Langmuir adsorption models were used for the mathematical description of the adsorption equilibrium and it was reported that experimental data fitted very well to Freundlich model, although they could be modelled by the Langmuir equation. Batch adsorption models, based on the assumption of the pseudo-first order and pseudo-second order mechanism, were applied to examine the kinetics of the adsorption. The results showed that kinetic data were followed more closely the pseudo-second order model than the pseudo-first order. The thermodynamic parameters such as, equilibrium constant (K), Gibbs free energy changes (Delta G degrees), standard enthalpy change (Delta H degrees) and standard entropy change (Delta S degrees) had been determined. The results show that adsorption of phenol on BPC is an endothermic and spontaneous in nature. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; adsorption; carbonisation; beet pulp carbon (BPQ; kinetic